The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/s1980-6574201900030010
|View full text |Cite
|
Sign up to set email alerts
|

Football training session rises creatine kinase but does not impair performance

Abstract: Determine the relationship between changes in oxidative stress markers, muscle damage, DOMS, and their relationship with performance in response to a session of football training during a 1-week recovery period of young football players. Methods: Nineteen young football players aged 16.7±1.0 years were included in the study. After initial evaluation for basal levels of oxidative stress and muscle damage markers, DOMS, and performance testing (Vertical Jump, Agility T-test, and RAST potency test), the athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, the great variability of ethnicities in local samples may have influenced the findings of the present study, since black individuals have higher concentrations of blood indicators of muscle damage 41 45 . Although the manual measurement of DOMS is a typical and valid protocol method 19 29 30 , DOMS measured in the present study has limitations, once the coefficient of variation in each measure was not calculated. The external load data quantified by GPS units must be analyzed with caution, since a tendency of underestimating data recorded at high speeds is common in this system 46 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, the great variability of ethnicities in local samples may have influenced the findings of the present study, since black individuals have higher concentrations of blood indicators of muscle damage 41 45 . Although the manual measurement of DOMS is a typical and valid protocol method 19 29 30 , DOMS measured in the present study has limitations, once the coefficient of variation in each measure was not calculated. The external load data quantified by GPS units must be analyzed with caution, since a tendency of underestimating data recorded at high speeds is common in this system 46 .…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, the elevation of CK, LDH and DOMS values observed immediately after the match (0 h) in both categories was, in a way expected, once the soccer match is able to generate physical and physiological wear in players, as these markers tend to remain elevated immediately after the soccer match 12 13 . Studies involving young soccer players that investigated blood markers of muscle damage and DOMS beyond time 0 h found that the blood marker of muscle damage remained elevated between 24 h 18 36 and up to 72 hours after the soccer match 19 . The results obtained in this study are similar, once blood markers of muscle damage remained elevated up to 24 h (U-15) and DOMS between 48 h and 72 h (U-15 and U-13 categories, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations